A record of two species of Acanthocephala (Echinorhynchida: Rhadinorhynchidae) from Red Sea fishes, Yemeni coastal waters - Al-Zubaidy, A.B.; Mhaisen, F.T. (Mesopotamian Journal of Marine Sciences, 2022)
A total of 198 specimens belonging to four fish species (Thunnus tonggol, Sphyraena barracuda, Pomadasys argenteus and Lutjanus gibbus) were purchased from Al-Mehwat fish market, Hodeidah, Yemen and inspected for acanthocephalan infections. Two acanthocephalans were detected. Juveniles of Serrasentis sagittifer were recovered from the intestine, pyloric caeca, body cavity, mesenteries and some internal organs of the above- named fishes with prevalence of 11.7%, 11.9%, 24% and 4.4%, respectively and a mean intensity of 3.3, 2.2, 5 and 2, respectively. Generally, male fishes showed higher values of infection in comparison with female fishes. Encysted juveniles of Gorgorhynchus sp. were recovered from the intestinal mesenteries of T. tonggol only with a prevalence of 3.3% and intensity of 2.5. The occurrence of the above-named acanthocephalans represents their first record from the Yemeni fishes of the Red Sea